Perancangan dan Implementasi Sistem Informasi Nasabah pada BSI KCP Gunung Tua Studi Kasus Data Nasabah - Laila Syarifah; Emmi Juwita Siregar; Afelia Anggraini; Rahmadhani Hasibuan; Riskha Armida Dewi (Lembaga Pengembangan Kinerja Dosen, 2025)
The development of information technology has influenced the way various sectors work, including banking. Previously, customer data management was done manually, which often led to data duplication and time delays. This study aims to create and implement a more effective customer information system at Bank Syariah Indonesia (BSI) Gunung Tua Branch Office (KCP), so that the data management process becomes faster and more accurate. This study used the R&D method with the Waterfall model. The system was created using the PHP or Laravel programming language and relied on a MySQL database. The results showed that the system was successfully created and implemented. This system supports two main types of users: Admin/Customer Service who can log in, manage customer data (input, change, delete, and search), and print reports; and Customers who can view personal data, monitor savings status, and create new accounts. In conclusion, this system has an integrated database structure (Admin, Customer, Account, Transaction tables) and successfully meets user needs, thereby increasing efficiency and accuracy in customer data management at BSI Gunung Tua KCP.